(untitled) (Cardiovascular Journal, 2022)
Brugada syndrome is inherited in an autosomal dominant pattern which is associated with ventricular fibrillation and sudden cardiac death in a patient with structurally normal heart. The diagnosis is clinched on characteristic EKG pattern of >2 mm ST segment elevation followed by negative T wave in right precordial leads V1,2 either occurring spontaneously or with pharmacological provocation with a sodium channel blocker. Prevalence of this disease varies by geographic location and sex with highest preponderance in South East Asian countries and in males. Among South-East Asian countries, there has been only one case report so far from Bangladesh and that too in a male patient. We present a case of female patient from Bangladesh with Brugada syndrome. We also report an association of Autism with Brugada syndrome in patient’s only female child. Cardiovasc j 2022; 15(1): 86-87